1987
DOI: 10.1016/s0013-9351(87)80242-6
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of organotin compounds—An overview

Abstract: As a consequence of the rapid expansion of the uses and applications of the organotin compounds, the concern about their environmental and health effects is increasing. The main subject of this overview is the current understanding of the mammalian toxicity of the organotin compounds. Four different types of target organ toxicity, namely neurotoxicity, hepatotoxicity, immunotoxicity, and cutaneous toxicity, are discussed in more detail. The effects of the organotin compounds on the mitochondfial and cellular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
131
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(136 citation statements)
references
References 100 publications
5
131
0
Order By: Relevance
“…In the case of the Stille reaction, an additional disadvantage is the very high toxicity of organotin compounds. [ 67 ] For these reasons, chemists seek alternative methods of biaryl bond synthesis that are free of the above-mentioned drawbacks. Such methods may include direct arylation via the C-H bond activation [ 66a ] and oxidative coupling of aromatic compounds through C-H/C-H activation.…”
Section: Reviewmentioning
confidence: 99%
“…In the case of the Stille reaction, an additional disadvantage is the very high toxicity of organotin compounds. [ 67 ] For these reasons, chemists seek alternative methods of biaryl bond synthesis that are free of the above-mentioned drawbacks. Such methods may include direct arylation via the C-H bond activation [ 66a ] and oxidative coupling of aromatic compounds through C-H/C-H activation.…”
Section: Reviewmentioning
confidence: 99%
“…Organotins, one of possible environmental hazards, exert specific toxic actions on respec tive target organs and organ systems such as the central nervous system and the immune system (1). Among the organotin toxicities, immunotoxicity has been histologically stud ied.…”
mentioning
confidence: 99%
“…Immune function studies with rats fed tributyltin or triphenyltin compounds revealed that the thymus-dependent immune responses were suppressed (5,6). In contrast with our know ledge concerning the immunotoxicity of orga notins in experimental animals fed these com pounds, there is little information on the cellu lar mechanism for their immunotoxicity (1,7). In this study, therefore, we have examined the effect of triphenyltin on mouse thymocytes us ing a flow-cytometer with fluorescent dyes for membrane potential and intracellular Ca 2+ ([Ca 2+]i).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 2(a) (d) oral LD 50 value for trimethyltin acetate in the rat is 9 µg/g [9] . The acute oral LD 50 values for many other organotin compounds in the rat are also at µg/g level.…”
Section: Gc-ms Analysismentioning
confidence: 92%